Prevalence of Mastitis and Phenotypic Characterization of Methicillin-Resistant in Lactating Dairy Cows of Selected Dairy Farms in and Around Adama Town, Central Ethiopia - Kaleab Tesfaye; Zemichael Gizaw; Aklilu Feleke Haile (SAGE Publishing, 2021)
Background: The emergence of Methicillin resistant Staphylococcus aureus (MRSA) poses a serious public health threat. Strains of Staphylococcus aureus resistant to β-lactam antibiotics are known as MRSA. MRSA has gained attention as community pathogen. MRSA has been increasingly reported as emerging problem in veterinary medicine. However, little is known in Ethiopia. This study was, therefore, conducted to identify MRSA, to determine its drug susceptibility patterns, and mastitis infection in dairy cattle in and around Adama town, Central Ethiopia. Methods: A cross-sectional study was conducted to estimate the occurrence of MRSA in mastitic dairy cows in and around Adama town, central Ethiopia. A total of 384 lactating cows were included from the conveniently selected dairy farms in the study area. Approximately 10 ml of milk was aseptically collected from clinical and subclinical mastitic cows into sterile universal bottles after discarding the first 3 milking streams. Then, Staphylococcus aureus was isolated using the conventional bacteriological procedure. Resistance to methicillin was detected using the Kirby-Bauer disc diffusion antibiotic susceptibility method. Oxacillin disc was used to detect methicillin resistant Staphylococcus aureus strains. Antimicrobial susceptibility test was conducted against MRSA strains using streptomycin (S, 10 µg), amoxicillin (Am, 25 µg), kanamycin (k, 30 µg), nalidixic acid (NA, 30 µg), oxytetracycline (OT, 30 µg) sulphonamide (S, 300 µg) and ceftriazole (CRO, 30 µg). Results: The study found that the prevalence of mastitis was 121(31.5%). Among this 37(30.6%) were clinical mastitis and 84 (69.4%) of them were sub-clinical mastitis. Of 121 mastitis cases, Staphylococcus aureus was isolated in 37 (30.6%) of mastitic cow milk samples. The prevalence of mastitis was significantly affected by breed, age, floor type and hygienic status of the milkers ( P  < .05). Moreover, 32.4% of Staphylococcus aureus isolates were resistant to oxacillin. A total of 75% percent of MRSA isolates were resistant to amoxicillin, 66.7% were resistant to oxytetracycline, and 50% were resistant to sulphonamide. However, 75% of MRSA isolates were susceptible to kanamycin, 58.3% were susceptible to streptomycin, and 50% were susceptible to nalidixic acid. Conclusion: The study revealed that relatively high number of strains are resistant to the antibiotics commonly used in the therapeutic protocol of many human and animal infections. Therefore, antimicrobial susceptibility test should be carried out at a regular basis and proper hygienic practices should be introduced at farm level. Creating public awareness about transmission, prevention and control of MRSA should also be considered.